Oxidative damage to biological macromolecules in Prague bus drivers and garagemen: impact of air pollution and genetic polymorphisms - Bagryantseva, Yana; Novotna, Bozena; Rossner, Pavel; Chvatalova, Irena; Milcova, Alena; Svecova, Vlasta; Lnenickova, Zdena; Solansky, Ivo; Sram, Radim J (Toxicology letters, 2010)
DNA integrity was investigated in the lymphocytes of 50 bus drivers, 20 garagemen and 50 controls using the comet assay with excision repair enzymes. In parallel, 8-oxo-7,8-dihydro-2'-deoxyguanosine and 15-F(2t)-isoprostane levels in the urine and protein carbonyl levels in the plasma were assessed as markers of oxidative damage to DNA, lipids and proteins. Exposure to carcinogenic polycyclic aromatic hydrocarbons (cPAHs) and volatile compounds was measured by personal samplers for 48 and 24h, respectively, before the collection of biological specimens. Both exposed groups exhibited a higher levels of DNA instability and oxidative damage to biological macromolecules than the controls. The incidence of oxidized lesions in lymphocyte DNA, but not the urinary levels of 8-oxodG, correlated with exposure to benzene and triglycerides increased this damage. Oxidative damage to lipids and proteins was associated with exposure to cPAHs and the lipid peroxidation levels positively correlated with age and LDL cholesterol, and negatively with vitamin C. The carriers of at least one variant hOGG1 (Cys) allele tended to higher oxidative damage to lymphocyte DNA than those with the wild genotype, while XPD23 (Gln/Gln) homozygotes were more susceptible to the induction of DNA strand breaks. In contrast, GSTM1 null variant seemed to protect DNA integrity.
Keywords: glutathiontransferasa; Polymorphism, Genetic; Glutathione Transferase; DNA Damage; Polycyclic Aromatic Hydrocarbons; Male; polymorfismus genetický; znečištění ovzduší; Oxidative Stress; Vasoconstrictor Agents; Guanine; Air Pollutants, Occupational; kometový test; vazokonstriktory; dinoprost; DNA-glykosylasy; xeroderma pigmentosum - protein skupiny D; polycyklické aromatické uhlovodíky; Volatile Organic Compounds; Air Pollution; Protein Carbonylation; Xeroderma Pigmentosum Group D Protein; mužské pohlaví; poškození DNA; Dinoprost; karbonylace proteinů; Lymphocytes; oxidační stres; DNA; Genetic Predisposition to Disease; guanin; peroxidace lipidů; Comet Assay; DNA Glycosylases; výfukové emise vozidel; Vehicle Emissions; lidé; Humans; těkavé organické sloučeniny; Lipid Peroxidation; lymfocyty; genetická predispozice k nemoci; látky znečišťující vzduch v pracovním prostředí